(untitled) (Anwer Khan Modern Medical College Journal, 2012)
Carcinoma breast is the leading cause death from cancer in women between 20-59 years.. The slow natural history makes it a potentially curable disease if presented early. Unfortunately the rural women in Bangladesh frequently present with late carcinoma breast. The objective of this study is to find out the stages of the disease when presented for the first time to a qualified doctor. The study shows that about 43% of our womenfolk present with late stage when the prognosis in terms of survival rate is not so optimistic. Even when they present with early breast cancer, most of them are at stage II. There is scope to improve the scenario by educating them on screening of breast carcinoma by self examination, mammogeusly, avoidance of risk factors and advantages of FNAC & biopsy from any breat lump. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10106 AKMMCJ 2012; 3(1): 10-12